Influence of gold nanoparticles on the photo-polymerization processes and structure in acrylate nanocomposites. (March 2015) - Burunkova, J.; Kokenyesi, S.; Csarnovics, I.; Bonyár, A.; Veres, M.; Csik, A.
Graphical abstract: Highlights: Parameters of photo-polymerization process were investigated in nanocomposites. The real time changes in the refractive index due to irradiation were monitored. Surface Plasmon Resonance imaging was used, which is a novel application of this platform. The nanoparticles have an influence on the polymer structure. The nanoparticles have an influence on some bonds change during the photo-polymerization. Abstract: Parameters of photo-polymerization process (induction time, rate and degree of conversion) as well as the change of the refractive index, micro hardness and so of the resulting structure were investigated in urethane–acrylate based nanocomposites. Monomers were functionalized by adding SiO2 and Au nanoparticles by means of direct incorporation. The structural changes due to addition of nanoparticles and photo-polymerization were investigated by micro-Raman spectroscopy and X-ray diffraction (XRD). The real time changes in the refractive index due to irradiation were monitored by Surface Plasmon Resonance imaging (SPRi), which is a novel application of this platform. It is established that these nanoparticles have an influence on the polymer structure and on the transformation of selected bonds during the photo-polymerization process. The plasmon field of gold nanoparticles has a specific additional influence on these changes. These effects can be used to enhance surface relief recording in such nanocomposites due to the photo-stimulated mass transport of the nanoparticles embedded to the polymer matrix.